Epidemiological study of skin diseases in Himatnagar - Shah, Bhuvnesh; Sheth, Keya Jayesh (International Journal of Research in Dermatology, 2019)
Background: The aim of the study was to identify the prevalence of skin diseases in the peripheral area of North Gujarat, India. Methods: It was retrograde OPD based study in which patients visiting skin department of GMERS, Himatnagar, were studied from 30 October 2017 to 30 October 2018. Results: Total 15042 patients, male were 53% and female were 47%. Fungal infection was the most common infectious diseases (16.6%) and eczema was the most common non infectious diseases (12.77%). Contact dermatitis accounted (10.49%). Xerosis (8.19%) was the most common in the patients who were in their 5th and 6th decade of life. Conclusions: Fungal infection was seen almost equally in male and female. Contact dermatitis was very common in females. Acne was seen predominantly in teenagers and adolescents due to hormonal changes.